Fault scarps and tectonic strain in young volcanic seafloor - Jie Chen; Javier Escartin; Mathilde Cannat (Earth and Planetary Science Letters, 2025)

Tectonic controls on melt production and crustal architecture during magma-poor seafloor spreading - Leila Mezri; Javier García-Pintado; Marta Pérez-Gussinyé; Zhonglan Liu; Wolfgang Bach; Mathilde Cannat (Earth and Planetary Science Letters, 2024)

Monitoring ecological dynamics on complex hydrothermal structures: A novel photogrammetry approach reveals fine‐scale variability of vent assemblages - Loïc Van Audenhaege; Jozée Sarrazin; Pierre Legendre; Garance Perrois; Mathilde Cannat; Aurélien Arnaubec; Marjolaine Matabos (Limnology and Oceanography, 2024)
We set out to characterize the fine‐scale processes acting on interannual dynamics of deep‐sea vent fauna by using a novel approach involving a 5‐yr time series of 3D photogrammetry models acquired at the Eiffel Tower sulfide edifice (Lucky Strike vent field, Mid‐Atlantic Ridge). Consistently, with the overall stability of the vent edifice, total mussel cover did not undergo drastic changes, suggesting that they have been at a climax stage for at least 25 yr based on previous data. Successional patterns showed consistency over time, illustrating the dynamic equilibrium of the ecological system. In contrast, microbial mats significantly declined, possibly due to magmatic events. The remaining environmental variability consisted of decimeter‐scale displacement of vent outflows, resulting from their opening or closure or from the progressive accretion of sulfide material. As a result, vent mussels showed submeter variability in the immediate vicinity of vent exits, possibly by repositioning in response to that fine‐scale regime of change. As former studies were not able to quantify processes at submeter scales in complex settings, this pioneering work demonstrates the potential of 3D photogrammetry models for conducting long‐term monitoring in the deep sea. We observed that the ability of mussels to displace may enable them to cope with changing local conditions in a stable system. However, the long‐term stability of mussel assemblages questions their capacity to withstand large‐scale disturbances and may imply a low resilience of these “climax” communities. This suggests that they may be particularly vulnerable to the negative effects of mining activities in hydrothermal ecosystems.

Evolution of enhanced magmatism at the ultraslow spreading Southwest Indian Ridge between 46°E and 53.5°E - Jie Chen; Tao Zhang; Huaiming Li; Chunhui Tao; Mathilde Cannat; Daniel Sauter (Tectonophysics, 2023)

Integrating Multidisciplinary Observations in Vent Environments (IMOVE): Decadal Progress in Deep-Sea Observatories at Hydrothermal Vents - Marjolaine Matabos; Thibaut Barreyre; S. Kim Juniper; Mathilde Cannat; Deborah Kelley; Joan M. Alfaro-Lucas; Valérie Chavagnac; Ana Colaço; Javier Escartin; Elva Escobar; Daniel Fornari; Jörg Hasenclever; et al. (Frontiers in Marine Science, 2022)
The unique ecosystems and biodiversity associated with mid-ocean ridge (MOR) hydrothermal vent systems contrast sharply with surrounding deep-sea habitats, however both may be increasingly threatened by anthropogenic activity (e.g., mining activities at massive sulphide deposits). Climate change can alter the deep-sea through increased bottom temperatures, loss of oxygen, and modifications to deep water circulation. Despite the potential of these profound impacts, the mechanisms enabling these systems and their ecosystems to persist, function and respond to oceanic, crustal, and anthropogenic forces remain poorly understood. This is due primarily to technological challenges and difficulties in accessing, observing and monitoring the deep-sea. In this context, the development of deep-sea observatories in the 2000s focused on understanding the coupling between sub-surface flow and oceanic and crustal conditions, and how they influence biological processes. Deep-sea observatories provide long-term, multidisciplinary time-series data comprising repeated observations and sampling at temporal resolutions from seconds to decades, through a combination of cabled, wireless, remotely controlled, and autonomous measurement systems. The three existing vent observatories are located on the Juan de Fuca and Mid-Atlantic Ridges (Ocean Observing Initiative, Ocean Networks Canada and the European Multidisciplinary Seafloor and water column Observatory). These observatories promote stewardship by defining effective environmental monitoring including characterizing biological and environmental baseline states, discriminating changes from natural variations versus those from anthropogenic activities, and assessing degradation, resilience and recovery after disturbance. This highlights the potential of observatories as valuable tools for environmental impact assessment (EIA) in the context of climate change and other anthropogenic activities, primarily ocean mining. This paper provides a synthesis on scientific advancements enabled by the three observatories this last decade, and recommendations to support future studies through international collaboration and coordination. The proposed recommendations include: i) establishing common global scientific questions and identification of Essential Ocean Variables (EOVs) specific to MORs, ii) guidance towards the effective use of observatories to support and inform policies that can impact society, iii) strategies for observatory infrastructure development that will help standardize sensors, data formats and capabilities, and iv) future technology needs and common sampling approaches to answer today’s most urgent and timely questions.

The EMSO Generic Instrument Module (EGIM): Standardized and Interoperable Instrumentation for Ocean Observation - Nadine Lantéri; Henry A. Ruhl; Andrew Gates; Enoc Martínez; Joaquin del Rio Fernandez; Jacopo Aguzzi; Mathilde Cannat; Eric Delory; Davide Embriaco; Robert Huber; Marjolaine Matabos; George Petihakis; et al. (Frontiers in Marine Science, 2022)
The oceans are a fundamental source for climate balance, sustainability of resources and life on Earth, therefore society has a strong and pressing interest in maintaining and, where possible, restoring the health of the marine ecosystems. Effective, integrated ocean observation is key to suggesting actions to reduce anthropogenic impact from coastal to deep-sea environments and address the main challenges of the 21st century, which are summarized in the UN Sustainable Development Goals and Blue Growth strategies. The European Multidisciplinary Seafloor and water column Observatory (EMSO), is a European Research Infrastructure Consortium (ERIC), with the aim of providing long-term observations via fixed-point ocean observatories in key environmental locations across European seas from the Arctic to the Black Sea. These may be supported by ship-based observations and autonomous systems such as gliders. In this paper, we present the EMSO Generic Instrument Module (EGIM), a deployment ready multi-sensor instrumentation module, designed to measure physical, biogeochemical, biological and ecosystem variables consistently, in a range of marine environments, over long periods of time. Here, we describe the system, features, configuration, operation and data management. We demonstrate, through a series of coastal and oceanic pilot experiments that the EGIM is a valuable standard ocean observation module, which can significantly improve the capacity of existing ocean observatories and provides the basis for new observatories. The diverse examples of use included the monitoring of fish activity response upon oceanographic variability, hydrothermal vent fluids and particle dispersion, passive acoustic monitoring of marine mammals and time series of environmental variation in the water column. With the EGIM available to all the EMSO Regional Facilities, EMSO will be reaching a milestone in standardization and interoperability, marking a key capability advancement in addressing issues of sustainability in resource and habitat management of the oceans.

Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Juan Jose Dañobeitia; Sylvie Pouliquen; Truls Johannessen; Alberto Basset; Mathilde Cannat; Benjamin Gerrit Pfeil; Maria Incoronata Fredella; Paola Materia; Claire Gourcuff; Giuseppe Magnifico; Eric Delory; Joaquin del Rio Fernandez; et al. (Frontiers in Marine Science, 2020)

A seafloor experiment to monitor vertical deformation at the Lucky Strike volcano, Mid-Atlantic Ridge - Valérie Ballu; Jérome Ammann; Olivier Pot; Olivier de Viron; Glenn S. Sasagawa; Gilles Reverdin; Marie-Noelle Bouin; Mathilde Cannat; Christine Deplus; Sébastien Deroussi; Marcia Maia; Michel Diament (Journal of Geodesy, 2009)

Monitoring and Observatories: Multidisciplinary, Time-Series Observations at Mid-Ocean Ridges - S. Kim Juniper; Javier Escartin; Mathilde Cannat (Oceanography, 2007)